Cover Image, Volume 114, Number 12, December 2017. Issue 12 (24th October 2017) - Huang, Zhuangrong; Lee, Dong‐Yup; Yoon, Seongkyu
Abstract : The cover image, by Zhuangrong Huang et al., is based on the Review Quantitative intracellular flux modeling and applications in biotherapeutic development and production using CHO cell cultures, DOI: 10.1002/bit.26384